Strengthening patriotism through YouTube platform - Ku Samsu, Ku Hasnita; Adnan, Zatul Himmah; Ab. Majid, Arfah (Centre for Global Open Access Learning, Immersive Technology & Quality Assurance, Universiti Sains Islam Malaysia, 2017)
Since YouTube platform emerges as one of the influential social media nowadays especially among the younger generation, it is good to be utilized as a medium in teaching and learning process to make boring subjects become more lively. For instance Kenegaraan Malaysia, a patriotism based subject which is vital in a context of nation building. Therefore, we use this platform to gain student’s attention through students centered learning activity such as producing patriotism themed video to be launched via YouTube. Certainly, the students will gain patriotism awareness while making the video, so will the viewers. Hence, patriotism spirit can be fostered in them appropriately.